2010
DOI: 10.3184/095422910x12838823648023
|View full text |Cite
|
Sign up to set email alerts
|

The complexation of aqueous metal ions relevant to biological applications: 2. Evaluation of simultaneous equilibria of poorly soluble zinc salts with select amino acids

Abstract: Simultaneous equilibria calculations were completed for seven aqueous zinc -ligand systems: zinc citrate plus either glycine, alanine, or serine, and zinc succinate plus either glycine, alanine, or serine, and zinc oxalate plus glycine. Mixed-ligand complexes were predicted for all but the zinc citrate-glycine system, and the proportion tends to peak around 5 molar equivalents of amino acid. Potential bioavailability of zinc appears to be increased by the inclusion of amino acids in solution, roughly in parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Thus, there is a great interest in identifying safer alternatives with superior bioavailability [1]. One potential group of candidates comprises zinc compounds containing organic moieties, which in general have shown better tolerability and bioavailability than the inorganic salts [10][11][12]. The exact organic ligand structure finally determines its main direction of use.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a great interest in identifying safer alternatives with superior bioavailability [1]. One potential group of candidates comprises zinc compounds containing organic moieties, which in general have shown better tolerability and bioavailability than the inorganic salts [10][11][12]. The exact organic ligand structure finally determines its main direction of use.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research in this group has shown that addition of glycine, alanine or serine to poorly soluble zinc complexes increases the solubility of the zinc complexes, and potentially the relative amount of zinc ions in the more bioavailable amino acid complexes in solution (Sobel et al, 2008). Mixed-ligand complexes are indicated from speciation calculations for some of the solutions (Sobel and Theophall, 2010). Exploration of copper(II) complexes may give more insight into formation of mixed-ligand complexes and amount of bioavailable copper(II) ions through simultaneous equilibria calculations and UV-Vis spectroscopy measurements.…”
Section: Copper Complexes Researchmentioning
confidence: 99%
“…However, they have been found to possess low bioavailability in organisms, but in contrast, results of several in vitro studies showed that the Zn(II) sulphate compounds have a higher potential to inhibit the bacterial growth and these results indicate that Zn(II) from inorganic Zn sources is toxic to microorganisms. Thus as a safer alternative are indicated candidates comprises Zn compounds containing organic moieties, which in general have shown better tolerability and bioavailability than the inorganic salts (Abendrot et al 2020 ; Sobel and Theophall 2010 ). However, generally little is known about the effects of different forms and quantities of Zn on the various bacteria and simultaneously although numerous reports have analysed the anti-bacterial effect of various Zn substances, limited studies have evaluated the inhibitory effect of Zn on biofilm formation.…”
Section: Introductionmentioning
confidence: 99%